Radicinin from Cochliobolus sp. inhibits Xylella fastidiosa, the causal agent of Pierce's Disease of grapevine. (August 2015) - Aldrich, Thomas J.; Rolshausen, Philippe E.; Roper, M. Caroline; Reader, Jordan M.; Steinhaus, Matthew J.; Rapicavoli, Jeannette; Vosburg, David A.; Maloney, Katherine N.
Graphical abstract: Radicinin (1 ) produced by a strain of Cochliobolus sp. isolated from grapevine inhibits Xylella fastidiosa in vitro, suggesting a possible mechanism for tolerance of Pierce's Disease. Highlights: Endophytes may confer grapevine with non-genetic tolerance of Pierce's Disease. A Cochliobolus sp. isolated from grapevine inhibits Xylella fastidiosa in vitro . Radicinin from Cochliobolus sp. shows dose-dependent inhibition of X. fastidiosa . Three radicinin derivatives were prepared to assess structure–activity relationships. Enzyme inhibition may occur via conjugate addition to carbon-10 of radicinin. Abstract: The fastidious phytopathogenic bacterium, Xylella fastidiosa, poses a substantial threat to many economically important crops, causing devastating diseases including Pierce's Disease of grapevine. Grapevines ( Vitis vinifera L.) planted in an area under Pierce's Disease pressure often display differences in disease severity and symptom expression, with apparently healthy vines growing alongside the dying ones, despite the fact that all the vines are genetic clones of one another. Under the hypothesis that endophytic microbes might be responsible for this non-genetic resistance to X. fastidiosa, endophytic fungi were isolated from vineyard cvs. 'Chardonnay' and 'Cabernet Sauvignon' grown under high Pierce's Disease pressure. A Cochliobolus sp. isolated from a Cabernet Sauvignon grapevine inhibited the growth of X. fastidiosa in vitro . Bioassay-guided isolation of an organic extract of Cochliobolus sp. yielded the natural product radicinin as the major active compound. Radicinin also inhibited proteases isolated from the culture supernatant of X. fastidiosa . In order to assess structure–activity relationships, three semi-synthetic derivatives of radicinin were prepared and tested for activity against X. fastidiosa in vitro . Assay results of these derivatives are consistent with enzyme inactivation by conjugate addition to carbon-10 of radicinin, as proposed previously.